Biologia reprodutiva de astyanax jacuihensis, bryconamericus iheringii, cyanocharax alburnus (characiformes: characidae) e corydoras paleatus (siluriformes: callichthyidae) na parte baixa da bacia do rio Piratini/RS - Ramalho, Graziela Rodriguez (Universidade do Vale do Rio dos Sinos, 2015)
Reproduction studies make it possible to determine type, location, spawning season and minimum size of individuals involved in this process. In this sense aim of this study was to describe the reproductive aspects of four populations of fish (Corydoras paleatus, Astyanax jacuihensis, Bryconamericus iheringii and Cyanocharax alburnus) the lower part of the Piratini/RS River basin. Sampling was carried out from January to March 2014 in seven places of sampling. Catches have been taken with trawl and hand net. The specimens were euthanized in a solution of eugenol for each liter de water for 1 minute. Subsequently, the material was fixed in 10% formalin for 48 hours and preserved in 70% alcohol. The identification at the species level was the Ichthyology Laboratory of UNISINOS. To analyze the reproductive biology of fish were analyzed morphometric data and the degree of maturation. The sexes were identified for all copies of the four species, based on a five-stage scale: Step A/immature; B/in maturation; Stage C/Mature Stage D/exhausted; Stadium E/Home. The results showed a total of 727 individuals belonging to 6 orders, 12 families, 28 genera and 38 species. Regarding the diversity index, Shannon-Wiener, equitability and dominance, the orders of Characiformes and Siluriformes dominated in wealth. For Siluriformes C. paleatus, analysis of the sex ratio did not differ significantly, 1: 1, whereas for Characiformes, B. iheringii and C.alburnus, significant differences of 3: 1 with the predominance of Female for these three species. The distribution of the capture site condition factor showed a strong increase and change the analyzed species, local 10:24, with negative allometric growth (b <3). The positive allometric growth (b> 3) was recorded in 12 sites, 21, 15, 35, 45, 53 and 80 in relation to the species C. paleatus, as well as the locations 12, 21, 23, 33 and 53 concerning order of Characiformes. Already at the locations 11, 12, 33 and 53, the Characiforms were negative allometric growth (b <3). Females in Stadium/C were found in places 10, 15, 24, 45, 53 and 80, corresponding to C. paleatus and the order of Characiformes enrolled low percentage majority of sites sampled. The frequency distribution of standard lengths for class showed that the range of length variation for Characiforms is comprised between 35 mm to 60 mm, and the Siluriformes between 20 mm to 60 mm. These results are important in ecological understanding and reproductive Piratini river fish.
Keywords: Reprodução; Fator de condição; Classe etária; Proporção; Bacia; Reproduction; Condition factor; Age group; Proportion; Basin; ACCNPQ::Ciências Biológicas::Biologia Geral